Pengaruh Kualitas Produk, Persepsi Harga dan Citra Merek terhadap Keputusan Pembelian - Nathasya Kusuma Wardani; Rina Ayu Vildayanti (Jurnal Rimba Riset Ilmu manajemen Bisnis dan Akuntansi, 2026)
This study aims to determine the influence of Product Quality, Price Perception, and Brand Image on Purchase Decisions in Shopee application users in South Jakarta. The population in this study is Shopee application users in South Jakarta who have made purchases in the last six months. The research sample was determined using the Non Probability Sampling method with the Lemeshow formula and obtained as many as 96 respondents who were considered to represent the characteristics of the population. Data was collected through a questionnaire with a Likert scale distributed through Google Form, then processed using Microsoft Excel 365 and SPSS software version 29 for descriptive analysis and hypothesis testing. The analysis techniques used included validity tests, reliability, classical assumption tests, multiple linear regression analysis, as well as t-tests and F-tests. The results showed that Product Quality, Price Perception, and Brand Image had a significant effect on Purchase Decisions in Shopee application users, both partially and simultaneously, which indicates the importance of marketing strategies based on product and brand values in improving consumer purchase decisions.